Ethnobotanical Diversity and Local Knowledge of Komak Plants (Fabaceae) in West Lombok Regency, Indonesia - Syilvia Fulan Tania; Sukiman; Rina Kurnianingsih; Nur Indah Julisaniah; Kurniasih Sukenti (Yayasan Siti Widhatul Faeha, 2026)
Komak plants are local legume species (Fabaceae) widely distributed in West Lombok Regency and traditionally utilized by local communities. Ethnobotanical studies are important to document the relationship between communities, plant resources, and environmental knowledge that supports sustainable use of local biodiversity. This study aimed to analyze the morphological diversity, utilization patterns, and environmental wisdom associated with komak plants in West Lombok. Data were collected through field observations and semi-structured interviews using purposive and snowball sampling techniques across ten sub-districts. The results identified three main komak species utilized by the community, namely Lablab purpureus, Phaseolus lunatus L., and Canavalia ensiformis (L.) DC. Within the Lablab group, three variants were recorded: L. purpureus subsp. uncinatus Verdc., L. purpureus subsp. purpureus, and L. purpureus var. typicus. Community utilization of komak was classified into six categories: food, traditional medicine, traditional ceremonies, ecological functions, economic functions, and animal feed. The highest Index of Cultural Significance (ICS) was recorded for L. purpureus subsp. purpureus (59), while C. ensiformis showed the lowest value (4). In addition, komak management reflects local environmental wisdom, including mutual cooperation during harvest, traditional seed storage, and ecological adaptation practices that support the sustainability of local agroecosystems.